To which extent a convalescent plasma therapy could be a benefit for COVID-19 patients? (Journal of Ideas in Health, 2020)
The emergence of an unprecedented pandemic SARS-COV-2 caused perplexed in the medical community because of a high infection rate and rising mortality among COVID-19 patients. Till now, there is no particular treatment for the disease; nevertheless, there is an extensive effort from scientists to find out an immediate therapeutic plan to show how to deal with the current situation. One of the solutions currently presented is Convalescence plasma (CP). Through this narrative review, we will shed light on CP's efficiency as a therapeutic agent for COVID-19, especially there is no proven vaccine or antiviral available up to date. CP could be considered one of the therapeutic approaches, but some limitations are still considered before it is established as a therapeutic agent. Along with evaluating CP from blood donors, the plasma companies could take future steps by manufacturing a target dose of globulins that contain standardized antibody, to reach the terms of health setting administering therapy.
Keywords: Convalescence plasma, COVID-19, Transfusion, Neutralizing Antibodies